The oral health status of healthy and obese children in a Turkish population: a cross-sectional study - ÖZGEN, İLKER TOLGA; POLAT, Gunseli Guven; Cehreli, Sevi Burcak; TASCILAR, Mehmet Emre; AKGUN, Ozlem Marti; ALTUN, Ceyhan; Ozgen, Ilker Tolga (My University, 2012)
Aim: To compare the oral health status of a group of obese and healthy Turkish children.